2009
DOI: 10.1002/jca.20202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blood group on idiopathic thrombotic thrombocytopenic purpura

Abstract: Thrombotic thrombocytopenic purpura (TTP) is a condition caused by deficiency of ADAMTS13 resulting in accumulation of ultra large Von Willebrand factor multimers (ULVWF), leading to micro thrombi in multiple organs. The varying susceptibilities of blood group antigens to ADAMTS13 have been demonstrated. A and B antigens are protective of VWF; and VWF purified from blood group O individuals has been shown to be cleaved faster by ADAMTS13 compared to VWF from blood group AB individuals. We proposed that there m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…There are two possible explanations for why our data are different from the two previous studies that failed to detect a difference between the observed and expected frequency of blood group O in patients with TTP. 1,2 First, the previous studies were retrospective reviews of available data in medical records at the participating hospitals; 1,2 this methodology could have created issues of patient selection. In contrast, our study was based on the prospective analysis of a population-based inception cohort of consecutive patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two possible explanations for why our data are different from the two previous studies that failed to detect a difference between the observed and expected frequency of blood group O in patients with TTP. 1,2 First, the previous studies were retrospective reviews of available data in medical records at the participating hospitals; 1,2 this methodology could have created issues of patient selection. In contrast, our study was based on the prospective analysis of a population-based inception cohort of consecutive patients.…”
Section: Discussionmentioning
confidence: 99%
“…S ubjects with blood group O have been postulated to be partially protected against the occurrence of thrombotic thrombocytopenic purpura (TTP) and therefore it was predicted that the observed frequency of blood group O among patients with TTP would be less than the expected frequency. 1,2 This postulate was based on previous observations that 1) plasma von Willebrand factor (VWF) levels are lower in subjects with blood group O compared to subjects with non-O blood groups; [3][4][5][6][7] 2) the clearance of VWF from plasma is faster in subjects with blood group O compared to subjects with non-O blood groups; 7 3) the rate of proteolysis of VWF by ADAMTS13 is greater in subjects with blood group O compared to subjects with non-O blood groups; 6,8 and 4) the level of ADAMTS13 activity in plasma in inversely related to the plasma VWF level. 9 Since the pathogenesis of TTP associated with severe ADAMTS13 deficiency is related to VWF-mediated microvascular thrombosis, 10 partial protection from TTP among subjects with blood group O was predicted because there may be less VWF in subjects with group O to contribute to VWFmediated thrombosis and the greater rate of proteolysis of VWF by ADAMTS13 in group O subjects may serve to partially protect these subjects from VWF-mediated thrombosis.…”
mentioning
confidence: 99%
“…This suggests that the combination of low ADAMTS13 and non‐O blood group is least favorable for a patient with respect to VWF processing 33 . However, two retrospective studies on the effect of ABO(H) blood group on TTP published recently showed conflicting results 35,36 . Zuberi and coworkers 36 hypothesized that there may be an association between blood groups and the risk of TTP, but differences in their study were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, two retrospective studies on the effect of ABO(H) blood group on TTP published recently showed conflicting results 35,36 . Zuberi and coworkers 36 hypothesized that there may be an association between blood groups and the risk of TTP, but differences in their study were not significant. Staropoli and coworkers 35 found no significant differences between group O and non‐O patients with respect to PLT count, lactate dehydrogenase concentration, maximum serum creatinine concentration, and total number of therapeutic plasma exchanges per episode and conclude that substrate‐related contributors to the highly variable phenotype and clinical course of TTP warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies presented relation between ABO groups, clearance of ultra large Von Willebrand factor multimers (ULVWF), deficiency of ADAMTS13 and risk of TTP development. [7] ADAMTS13 is a circulating zinc metalloprotease, responsible to cleave the ULVWF, thereby the multimers become progressively smaller due to cleavage by ADAMTS13. Deficiency of ADAMTS13 leads to a shift of plasma ULVWF multimers to larger sizes, adhesion with platelets and its aggregation, leading to endothelial injury with activation of thrombosis cascade.…”
Section: Discussionmentioning
confidence: 99%